An analysis on the effectiveness of community policing strategies on the methamphetamine trade in Tonga : a research project presented in partial fulfilment of the requirements for the degree of Master of International Development, School of People, Environment and Planning, Massey University, Manawatu, New Zealand - Naisali, Seimoana (Massey University, 2022)
Police reform in small island developing countries has seen the increasing implementation of the community policing strategies as a means to achieve trust and confidence of Police within the community. Over the past two decades, the Pacific Islands have adopted a community-oriented policing approach over more hardened methods of law enforcement found in traditional policing because its strategies offer a more loosened approach to restoring justice and peace in the community. However, there have been claims that foreign assistance provided by donor countries to support policing in the Pacific has introduced new problems for recipient countries, particularly in the areas of policy design, implementation and suitability. This report analyses the effectiveness of community policing strategies in Tonga relating to methamphetamine, and the ways in which New Zealand provides aid to support and improve Tonga’s capacity and capability to tackle the issue. Increased reports of methamphetamine around Tonga have been increasingly evident in media headlines and Police reports. The debate in this research draws upon findings in the literature, semi-structured interviews and document analysis through Tonga Police’s current policy reviews. The findings also examine the suitability of foreign priorities in the local context and how improvements can be made to increase the efficacy and efficiency of Tonga Police. This research suggest that while New Zealand’s proactiveness in Tonga has seen slow but progressive results, its drug related strategies lack input and direction from local government and Tonga Police. A shift towards culturally suitable policing strategies focused on improving community wellbeing through grassroots initiatives such as rehabilitation, training and education is urgently required. The research argues for more collaborative cross-sector efforts between local government agencies and external organisations whose involvement can help to alleviate the strain on Police resources whilst upholding and improving community wellbeing.
Keywords: 440211 Police administration, procedures and practice; 451801 Pacific Peoples and the law